Evaluation of mechanical properties of four different carbon/epoxy composites used in aeronautical field - Paiva,Jane Maria Faulstich de (2005)
Four families of carbon fiber reinforced composites (CFRC) used in aeronautical industry were evaluated by flexural and interlaminar shear tests. It is also characterized three families of non-conditioned and conditioned CFRC by compression test. The composites were obtained by hand lay-up process in autoclave by using prepregs based on epoxy matrices (F155 and F584) and carbon fiber fabric reinforcements (PW-"Plain Weave" and 8HS-"Eight Harness Satin"). The F155-epoxy matrix was cured at 121 °C and the F584-epoxy type at 177 °C. After molding, the laminates were cut in specimens attending the ASTM D790 for the flexural test, the ASTM D2344 for the interlaminar shear test (ILSS) and the ASTM D3410 for the compressive test. The compressive tests were performed for testing the specimens before and after hygrothermal conditioning. The results show that the F584-epoxy matrix laminates present higher mechanical properties when compared to the F155-epoxy ones. The shear-tested samples observed by scanning electron microscopy and that ones tested in flexural, analyzed by stereoscopy, revealed that the fractured surfaces present typical aspects. The compressive results show that the hygrothermal conditioning caused the decrease of the compressive strength in, approximately, 8-20% depending on the laminate type. The failure modes of the tested specimens were evaluated showing good agreement with the literature.